Study and implementation of a gait rehabilitation system with capability for mobility and gait pattern generation - Lim, Hup Boon (2012)
Human motor performance appears to be remarkably flexible and easy. Yet, the underlying neuronal operations are only vaguely understood, even for well-studied movements. However, the walking capabilities that seem to be an easy task for healthy person often become a major problem for those with disability, especially those who have lost the capability of walking after spinal cord injury or stroke. A brief introduction of spinal cord injury and stroke is provided for an insight of the potential gait disability after the lesion. Therapist assisted body weight supported gait rehabilitation is a modern gait rehabilitation method developed for gait rehabilitation mainly for spinal cord injury and stroke patients. However, this method is labor intensive and requires at least three therapists for each patient. In view of this issue, robotic systems have been introduced for body weight supported gait rehabilitation to reduce the intensive labor involved. Such systems, e.g., Lokomat, KineAssist, WalkTrainer, and HapticWalker are reviewed in depth. The pro and cons of these systems are also summarized.The review on the state of the art in robotic assisted gait rehabilitation revealed that there is a need for development of a new gait rehabilitation methodology. The proposed gait rehabilitation methodology suggests that gait rehabilitation features such as natural pelvic motion assistance, lower limb gait locomotion assistance, and body weight support shall be provided together in the context of over-ground walking. The methodology also proposes a subject specific gait pattern planning.